A comparison of the preferred learning styles of year 5, year 7 and year 9 students in science using the science laboratory environment inventory (SLEI) and a cooperative learning unit of work based on multiple intelligences - Pfeiffer, Linda Gay (Curtin University, 2011)
Research has shown that students are increasingly disinterested in science (Gallagher, 1996). One only has to walk through the corridors of almost any secondary school to realise that students find science boring, irrelevant, not applicable and abstract. There is little doubt that if the science learning environment was made interesting and relevant to students, there could be a shift from the growing “unpopularity” of science. This study compared the preferred learning styles of 59 Year 5, 113 Year 7 and 113 Year 9 students in science using the Science Laboratory Environment Inventory (SLEI) and a Grid of a cooperative learning unit of work on Natural Events based on Multiple Intelligences. The study focussed particularly on students’ perceptions of science, improving the classroom learning environment and whether gender played a role in preferred learning style.From this investigation, formulating classroom learning environments where studentcohesiveness is high and learning activities are varied is paramount for improving student (and hence future generations) interest in science. Teachers of Year 5, Year 7 and Year 9 science students need to think “outside the square” and embrace a style of teaching that provides firm rules as well as a friendly environment. Older students should be exposed to the type of classroom that they experienced in lower primary school – clear and simple rules, fun, exciting, relevant, and memorable. It’s time for teachers to “set young minds on fire”.